[tex]2 log 3x + log (x + 1) - log (x^2 - 1)[/tex] is simplified as [tex]log (\frac{9x^2}{(x-1)})[/tex] .
Step-by-step explanation:
Here we have , 2 log 3x + log (x + 1) - log (x² - 1) or[tex]2 log 3x + log (x + 1) - log (x^2 - 1)[/tex]
⇒ [tex]2 log 3x + log (x + 1) - log (x^2 - 1)[/tex] { [tex]alogb = logb^a[/tex] }
⇒ [tex](log (3x)^2) + log (x + 1) - log (x^2 - 1)[/tex] { [tex]loga -logb = log(\frac{a}{b})[/tex] }
⇒ [tex](log (3x)^2) + log (\frac{(x + 1)}{(x^2 - 1)})[/tex]
⇒ [tex]log 9x^2 + log (\frac{(x + 1)}{(x^2 - 1)})[/tex]
⇒ [tex]log 9x^2 + log (\frac{(x + 1)}{(x-1)(x+1)})[/tex]
⇒ [tex]log 9x^2 + log (\frac{1}{(x-1)})[/tex]
⇒ [tex]log 9x^2 + (-1)log(x-1)[/tex] { [tex]log(\frac{1}{b}) = -logb[/tex] }
⇒ [tex]log 9x^2 -log(x-1)[/tex]
⇒ [tex]log (\frac{9x^2}{(x-1)})[/tex]
[tex]2 log 3x + log (x + 1) - log (x^2 - 1)[/tex] is simplified as [tex]log (\frac{9x^2}{(x-1)})[/tex] .